2021
DOI: 10.24911/ejmcr/173-1605961968
|View full text |Cite
|
Sign up to set email alerts
|

Full recovery of a patient with COVID-19-induced acute kidney injury

Abstract: Background: In this report, we discuss the diagnosis and management of a case of COVID-19-induced acute kidney injury (AKI). Case Presentation: A 58-year-old male with PCR-based COVID-19 diagnosis (at a specialized hospital, Minia, Egypt) was admitted and received supportive medications along with corticosteroids and hydroxychloroquine. After 2 days, the patient developed tachypnoea and desaturation. Therefore, he was transferred to the intensive care unit with a continuous positive airway pressure. On the thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Colestyramine, activated charcoal, and colestipol have been validated as efficacious management modalities in such situations, which have been proven to be acting by binding to digoxin within the gastrointestinal tract and reducing its absorption. [13][14][15][16] This has significantly lead to an increase in the systematic clearance of the compound. In addition, it enhanced excretion within the stool.…”
Section: Management Of Digitalis Toxicitymentioning
confidence: 99%
“…Colestyramine, activated charcoal, and colestipol have been validated as efficacious management modalities in such situations, which have been proven to be acting by binding to digoxin within the gastrointestinal tract and reducing its absorption. [13][14][15][16] This has significantly lead to an increase in the systematic clearance of the compound. In addition, it enhanced excretion within the stool.…”
Section: Management Of Digitalis Toxicitymentioning
confidence: 99%
“…4 However, the COVID-19 disease can be severe in some cases where there might be severe organ damage leading to some complications related to the lungs, kidney, liver, and central nervous system. [5][6][7][8][9][10] Moreover, pulmonary manifestations remain the most common manifestations that can be observed among these patients and some studies have reported that the pulmonary findings can be used to diagnose or suspect the infection, and predict the prognosis of the disease. 7 CT of the chest has been previously reported as an efficacious approach for the early diagnosis and suspicion of COVID-19 infection, as diagnosis with other modalities is usually timeconsuming and cannot detect the disease within the early stages.…”
Section: Introductionmentioning
confidence: 99%